Subcutaneous dirofilariosis (Dirofilaria repens): an infection spreading throughout the old world - Claudio Genchi; Laura Kramer (Parasites & Vectors, 2017)
Abstract Background Two main Dirofilaria species infect dogs: D. immitis and D. repens. While D. immitis has a worldwide distribution, D. repens is currently found only in Europe, Asia, and Africa. Adult D. repens are located in subcutaneous tissues of natural hosts where they survive for long periods of time. First-stage larvae, microfilariae, circulate in the peripheral bloodstream, where they are taken up by the mosquito intermediate hosts. Infected mosquitoes then transmit infective third-stage (L3) larvae to new hosts through the blood meal. In dogs, most infections are asymptomatic, although cutaneous disorders such as pruritus, dermal swelling, subcutaneous nodules, and ocular conjunctivitis can be observed. Currently, two factors have increased the concerns about this parasitic infection 1) its spread throughout the European countries and to other continents and its prevalence in dog populations, where in some cases it has overcome D. immitis; and 2) its zoonotic potential, which is much greater than that of D. immitis. Results Different hypotheses can be put forward to explain these concerns. First, climate change has allowed more favorable conditions for survival of culicid vectors. Second, accidental hosts such as humans may have a less efficient immune reaction against a parasite that is located in subcutaneous tissues, and thus less exposed to the host’s immune response than, for instance, D. immitis. Furthermore, the absence of clinical signs in the majority of canine infections and the difficulty in diagnosing the infection, due to the lack of serologic tests and thus the reliance on the identification of microfilariae and differentiation from D. immitis to confirm the presence of the parasite, favor the further spread of this species. Finally, among the macrocyclic lactones currently used to prevent heartworm infection, only moxidectin has been found to be fully effective against the infective larvae transmitted by mosquitoes and partially effective (efficacy 96%) against adult D. repens in experimental studies. Conclusions Dirofilaria repens infection is much more difficult than D. immitis to diagnose and control in the reservoir population (microfilaremic dogs). In addition, lack of familiarity with D. repens infection could lead to lack of vigilance underestimation for this parasite. The number of human cases in Europe and Asia is currently a serious public health concern. Medical doctors and veterinarians must collaborate closely for better control and surveillance of D. repens infection.